Helkimo and Craniomandibular Indices in the Classification of Temporomandibular Disorders. A Comparative Study. Issue 3 (2nd October 2015) - Rodrigues, Alex de Freitas; Kondo, Camila Assanoma; Procópio, Antonio Silvio F.; Luz, João Gualberto C.
Abstract: Objectives: Temporomandibular disorders (TMD) may present with diverse symptoms and multiple signs. Thus, the use of indices allows reliable quantification of the signs and symptoms of the TMD based on signs and symptoms and standardized clinical examination. The purpose of this study was to compare the results obtained using the anamnestic and clinical dysfunction Helkimo indices and Fricton's Craniomandibular Index (CMI) in the same group of patients with TMD. Material and methods: Thirty patients (28 women and 2 men, mean age 34.0 years) with diagnosis of TMD according to the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) were evaluated to obtain the Helkimo indices and CMI. Statistical analyses were performed using the Statistical Package for Social Sciences (SPSS) version 19.0. The data were submitted to the Spearman correlation test. Results: There was a statistically significant correlation between the Helkimo anamnestic index and the CMI ( p = 0.019) and between the Helkimo clinical dysfunction index and the CMI ( p = 0.001). Comparing the component items of the Helkimo clinical dysfunction index and the CMI, there was a correlation in most crosses. Conclusions: It was concluded that there was a statistically significant correlation between the anamnestic and clinical dysfunction Helkimo indices and Fricton's CMI, with correlation in most of their subitems. Thus, both indices – Helkimo or Fricton's – are suitable for the evaluation of a specific case of TMD. However, the CMI is more detailed in the composition of some of its subitems, which could lead to a more complete assessment.